STUDI KEDUDUKAN DAN PERAN DEWAN PENGAWAS SYARI’AH DI KOPERASI SYARI’AH - Desi Isnaini (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Law no. 1 Year 2013 on Microfinance institutions has given option for Baitul Maal and Shari'ah cooperatives to determine their legal umbrella if their business is engaged in Financial Services regulator is the Financial Services Authority, but if they choose to become a regular Shari'ah cooperative then they under the regulator of the Ministry of Cooperatives and UMKM. The position of the Sharia Supervisory Board is very clear because it is within the institutional structure of Shari'ah cooperatives, it's just that the rules that exist about the implementation of the supervisor still require clear and detailed guidelines. While the role of the Supervisory Board of Shari'ah in supervising the implementation of Shariah principles in the Cooperative there are several things that must be emphasized and made more detailed and detailed guidelines